2016
DOI: 10.1002/cmdc.201600076
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated Trivalent Mannobioses: Chemical Modification, Structural Elucidation, and Biological Evaluation

Abstract: People suffering from allergies can be treated with repeated injections of increasing amounts of a specific allergen. This type of specific immunotherapy is currently the only way to treat the underlying pathological immune response associated with an allergy. The approach can afford long-lasting protection, but the process takes 3-5 years, can produce allergic reactions, and in severe cases treatment is often aborted due to anaphylaxis. However, treatment can be optimized with the use of specific adjuvants th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…We have earlier shown in vitro that TADM beneficially affects cytokine production of peripheral blood cells among allergic subjects and favours T helper 1 and T regulatory cell type responses . Previously, we have also shown that, in contrast to CpG and MPLA, TADM does not appear to function as TLR agonist . In addition, our studies in an acute murine asthma model proved that TADM significantly suppresses allergen‐specific IgE production and increases mRNA expression of IFN‐γ in lung tissues …”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…We have earlier shown in vitro that TADM beneficially affects cytokine production of peripheral blood cells among allergic subjects and favours T helper 1 and T regulatory cell type responses . Previously, we have also shown that, in contrast to CpG and MPLA, TADM does not appear to function as TLR agonist . In addition, our studies in an acute murine asthma model proved that TADM significantly suppresses allergen‐specific IgE production and increases mRNA expression of IFN‐γ in lung tissues …”
Section: Discussionsupporting
confidence: 53%
“…Triacedimannose is a trivalent glycocluster, consisting of fully acetylated β‐(1→2)‐linked mannobiose units, designed to mimic C. albicans cell wall mannan oligosaccharides, which are known to possess immunostimulatory properties . We have earlier shown in vitro that TADM beneficially affects cytokine production of peripheral blood cells among allergic subjects and favours T helper 1 and T regulatory cell type responses . Previously, we have also shown that, in contrast to CpG and MPLA, TADM does not appear to function as TLR agonist .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation